2011
DOI: 10.1074/jbc.m110.184762
|View full text |Cite
|
Sign up to set email alerts
|

Munc13-4 Restricts Motility of Rab27a-expressing Vesicles to Facilitate Lipopolysaccharide-induced Priming of Exocytosis in Neutrophils

Abstract: LPS is an efficient sensitizer of the neutrophil exocytic response to a second stimulus. Although neutrophil exocytosis in response to pathogen-derived molecules plays an important role in the innate immune response to infections, the molecular mechanism underlying LPS-dependent regulation of neutrophil exocytosis is currently unknown. The small GTPase Rab27a and its effector Munc13-4 regulate exocytosis in hematopoietic cells. Whether Rab27a and Munc13-4 modulate discrete steps or the same steps during exocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 29 publications
3
88
0
Order By: Relevance
“…First, we determined the subcellular distribution of MUNC13-4 in relationship to that of flavocytochrome b 558 by cell fractionation and confocal microscopy. We found that endogenous MUNC13-4 colocalizes and cofractionates with organelles expressing gp91 phox and p22 MUNC13-4 regulates vesicular trafficking and has been proposed to regulate vesicular tethering (47), docking (30), and fusion (33) during exocytosis. To analyze whether the deficiency in MUNC13-4 is associated with abnormal distribution or mobilization of flavocytochrome b 558 -expressing organelles, we utilized TIRF microscopy and analyzed the localization of flavocytochrome b 558 -expressing granules in relationship to the plasma membrane in MUNC13-4 KO cells.…”
Section: Munc13-4 Regulates the Number Of P22mentioning
confidence: 99%
See 4 more Smart Citations
“…First, we determined the subcellular distribution of MUNC13-4 in relationship to that of flavocytochrome b 558 by cell fractionation and confocal microscopy. We found that endogenous MUNC13-4 colocalizes and cofractionates with organelles expressing gp91 phox and p22 MUNC13-4 regulates vesicular trafficking and has been proposed to regulate vesicular tethering (47), docking (30), and fusion (33) during exocytosis. To analyze whether the deficiency in MUNC13-4 is associated with abnormal distribution or mobilization of flavocytochrome b 558 -expressing organelles, we utilized TIRF microscopy and analyzed the localization of flavocytochrome b 558 -expressing granules in relationship to the plasma membrane in MUNC13-4 KO cells.…”
Section: Munc13-4 Regulates the Number Of P22mentioning
confidence: 99%
“…The cells were stored in unsolidified water-based mounting medium (refractive index, 1.37) or PBS until analyzed. TIRF microscopy experiments were performed using a 100ϫ 1.45 numerical aperture TIRF objective (Nikon) on a Nikon TE2000U microscope custom modified with a TIRF illumination module as described (30). Images were acquired on a 14-bit, cooled charge-coupled device camera (Hamamatsu) controlled through NIS-Elements software.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations